Sufi Order of Kubrovia and Naqshbandi Are an Integral Part of Pilgrimages Tourism In Central Asia - I.V. Mukhamednazarova; Xoschu Elvira; T.M. Nizamutdinov (Indonesian Journal of Cultural and Community Development, 2020)
This study aims to reveal the philosophical thought of the Sufi orders of Kubrovia and Naqshbandi, as well as their current state abroad. In recent years, the tourism potential of Uzbekistan has been developing rapidly. According to statistics, in 2019, 6.748 million peoples visited Uzbekistan, which is much more compared to 2018 (5.346 million). Most tourists came from the CIS countries and neighboring countries. It is of great interest to tourists if we are talking about representatives of Muslim countries, both earlier and today, represent the pilgrimage places of our main cities of the republic. It is said that if graceful light descends from heaven to all cities of the world, then in Bukhara it rises from the earth with a pillar to heaven, and the source of this light is a large number of shrines that are on this blessed land. In this article, we will analyze the origins of the Sufi movements that existed in Uzbekistan. Indeed, thanks to them, religious tourism is actively developing in our country, or as it is customary to call it in the East, “ziyorat” literally “visiting holy places”.